Validity and reliability of the Box and Block Test for individuals with schizophrenia spectrum disorder - Su, Jing-Wen; Chen, Hsiang-Yu; Li, Kuan-Yi (Frontiers in Psychiatry, 2025)
BackgroundThe Box and Block Test (BBT) is recognized for assessing manual dexterity; however, its reliability and validity, specifically for individuals with schizophrenia spectrum disorders, remain underexplored. The objective of this study was to establish the validity and reliability of the BBT for individuals with schizophrenia spectrum disorders.MethodsThis cross-sectional observational study was conducted in community psychiatric rehabilitation centers. The participants were individuals with schizophrenia spectrum disorders, ranging in age from 20 to 65 years. A total of seventy participants underwent the BBT, Purdue Pegboard Test (PPT), and Minnesota Manual Dexterity Test (MMDT) to assess manual dexterity. The validity and reliability of the BBT were evaluated using Pearson correlation coefficient and intraclass correlation coefficient (ICC).ResultsThe BBT strongly correlated with the PPT across all subtests (p < 0.001) and demonstrated moderate to strong correlations with the MMDT, except for the two-hand turning subtest. Intra- and inter-rater reliability ICCs ranged from 0.80 to 0.95 (p < 0.05), and test-retest reliability ICCs were between 0.70 and 0.71 (p < 0.001). A notable moderate negative correlation was observed between manual dexterity performance and both the total score and the positive symptom subscale of the Brief Psychiatric Rating Scale-Chinese version (BPRS-C) (r = -0.42 ~ -0.56, all p <0.001). Additionally, there were significant low correlations between the BBT and monthly income (r = 0.29 ~ 0.30, all p = 0.01).ConclusionsBBT has good validity and reliability in individuals with schizophrenia. Thus, BBT has emerged as a more favorable option for clinical assessment, avoiding the limitations that hamper PPT and MMDT. The simplicity and rapidity of BBT, combined with the provision of normative data, support the creation of customized rehabilitation plans that are crucial for rehabilitation focused on vocational and daily living skills.